The Potential of the Cultural Landscape of Yeh Gangga Temple in Perean Village, Tabanan Regency as a Tourist Attraction - Bagus Suryada I Gusti Agung (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
Yeh Gangga Temple located in Perean Village, Tabanan Regency is a cultural landscape that has been designated as a cultural heritage, so it has many interesting things. This temple is located close to the route to the Bedugul tourist area, but has not been visited by many tourists. This temple has not been managed as a tourist attraction. The potential of tourist attraction elements needs to be explored, as an initial step in realizing the cultural landscape of Yeh Gangga Temple as a tourist attraction. This research is a qualitative research. Data collection was carried out by means of literature study, interviews, and field exploration. The analysis method uses the literature review method, and is presented descriptively. The results of this study conclude that Yeh Gangga Temple is an associative cultural landscape. The tourist attractions in this cultural landscape are tradition, history, architecture, people's way of life, and religion. These tourist attractions have value, uniqueness, and beauty. The elements of the cultural landscape of Yeh Gangga Temple which are the syncretism of Hindu-Buddhist concepts are uniqueness that fosters the variety of tourist attractions in Bali.